Service Use 110 by Malang City Police Satlantas in Increasing the Speed of Handling Traffic Accidents - Rinaldi, Moh. Nur (Advances in Police Science Research Journal, 2024)
We can actually minimize deaths and material losses resulting from traffic accidents by handling them quickly and appropriately. This research aims to identify, describe and describe efforts to utilize the 110 service so that it can provide benefits in increasing the speed of handling traffic accidents. In the analysis, researchers used the 6M management theory (Man, Money, Material, Method, Machine, and Market), POAC management theory which consists of planning, organizing, implementing and controlling, as well as public service theory. The concepts used in this research are the concept of utilization, the concept of service 110, and the concept of handling traffic accidents. This type of research is field research using a qualitative approach with data collection techniques in the form of interviews, document study and observation. Based on research results, the 110 service is still not widely known and utilized by the public in reporting and notifying traffic accidents. The implementation of the 110 service is still not in accordance with Perkap No. 1/2018. And the handling process is still limited in terms of human resources, quantity of infrastructure and spending more funds than the available budget.